Teaching-led research? Exploring the digital agencies of software in qualitative research - Wright, Steve; Bhatt, Ibrar (Proceedings of the International Conference on Networked Learning, 2016)
This work-in-progress paper explores the intersection of technologies and software with the practices, of qualitative research and qualitative data analysis. Computer aided qualitative data analysis software (CAQDAS) packages such as ATLAS.ti, NVivo and HyperRESEARCH are the focus of competing claims and critiques. We explore the positioning, continuities and disjunctures between manufacturers promoting their software, positioning in teaching and training materials and a range of views in the literature from critical to laudatory, as well as their prevalence in research on networked learning. The pre-eminence and influence of expository writing and paucity of empirical research underscore the relevance and potential contribution of this project, We argue that part of that contribution comes from drawing on insights from science and technology studies (STS) which offer a well-developed vocabulary and set of approaches for exploring the agencies and mediation of technologies in the practices of research. The initial stages of the research project are outlined including online participant recruitment via facebook, methods of screen-share remote interviewing to generate rich data exploring software use, and incorporating accounts of researchers’ practices. Their transformation and mediation to become “data” through different software packages are briefly explored. Drawing on Latour’s model of the two-faced Janus of science with which contrasts “science in the making" with “ready made science” we turn to consider ways in which this project can invert the usual trope of University education as research led, asking instead how a research project could become teaching-led. We briefly explore some of the initial approaches and opportunities this has created for opening up the black-box of research practices and shifting software training methods to engage learners in a process of discovery as “learning in the making” rather than being tasked with stepping through fixed frames of “ready made teaching”.